6 - Children at Risk: A Study of the Psychosocial Impact of HIV on Orphans and other Vulnerable Children in Benin - Østergaard, Lise Rosendal; Meyrowitsch, Dan W. (Africa Development, 2021)
This paper describes the effect of parental HIV on the life of children in Benin. A total of 2,043 children aged from 10 to 16 were surveyed on health, diet, violence, school attendance and psychosocial state. The results indicate that, while Beninese children who have had a parent living with HIV are not necessarily subjected to different economic and material conditions than those who have not, they do experience a much greater lack of psychosocial support. In contrast to children whose parents are not known to have HIV, these affected children are less prone to general illness (OR=0.69, 95 per cent CI 0.55-0.86). However, when they are sick, HIV-affected children are significantly more likely to undertake self-treatment (OR=1.38; 95 per cent CI 1.04-1.86) and more likely to work (OR=1.65, 95 per cent CI 1.04-2.60). They are also offered fewer meals than unaffected children (OR=1.94; 95 per cent CI 1.52-2.47). With respect to psychosocial fac- tors, the data suggest that children who have had a parent with HIV have signifi- cantly higher levels of psychological distress than those who have not. Govern- ments and civil society organisations need to address not only the material deprivation, especially hunger, of children thus affected by HIV, but also their need for social services.